2011
DOI: 10.1111/j.1440-1835.2011.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine necklace‐chain Fragilariaceae (Bacillariophyceae) from Guam, including descriptions of Koernerella and Perideraion, genera nova

Abstract: Light microscopy (LM) and scanning electron microscopy (SEM) studies of necklace-chain forming colonial diatoms from benthic habitats in Guam revealed five species. Bleakeleya notata (Grunow in Van Heurck) Round is widespread and well-known. Asterionella notata var. recticostata Körner has been reported only twice before; we describe the plastids for the first time. On phylogenetic grounds we assign A. notata var. recticostata to a new genus, Koernerella, and emend the description of Bleakeleya. Three new spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The term “ocellus” has been used to describe several different structures, such as the apical pore field in the araphid pennate diatom Bleakeleya Round and is discussed in Lobban et al. ().…”
mentioning
confidence: 99%
“…The term “ocellus” has been used to describe several different structures, such as the apical pore field in the araphid pennate diatom Bleakeleya Round and is discussed in Lobban et al. ().…”
mentioning
confidence: 99%
“…Observations of fresh and acid cleaned materials were carried out at U. Guam and U. Texas, Austin, as in previous work (Lobban et al. , , Ashworth et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…) and description of several new species has led to improved understanding of some little‐known genera (Lobban et al. , , Ashworth et al. , Lobban ) and contributed to phylogenetic studies (Theriot et al.…”
mentioning
confidence: 99%
“…There may be at least five species in the Laurentian Great Lakes. A later study that included additional more closely related groups, showed that the two subgenera, although distinct, were not necessarily one another's sister group, with Odontidium instead most closely related to Tabellaria and Tetracyclus (Williams, 1989;Lobban et al, 2011). Frustules are rectangular in girdle view.…”
Section: Tabellarialesmentioning
confidence: 98%
“…All of these genera are, according to recent molecular data, most closely related among themselves and a few other marine "araphid" groups (Lobban et al, 2011). The freshwater species of Asterionella, according to both morphological data and molecular data (Williams, 1989;Lobban et al, 2011), are most closely related to other freshwater genera, such as Diatoma, Odontidium, and Tabellaria.…”
Section: Tabellarialesmentioning
confidence: 99%